KAMISEDEKAH Program Majoring in Sharia Economics in The Welfare of The People - Jannah, Mukhlishotul; Hadiyyin, Ikhwan (ISLAMICONOMIC: Jurnal Ekonomi Islam, 2023)
Alms are small acts of kindness meant to help others and promote social empathy. The KAMISEDEKAH program, run by the Department of Sharia Economics at UIN Sultan Maulana Hasanuddin Banten, aims to create job opportunities, reduce crime, and strengthen community bonds. This study highlights key aspects of the program. The KAMISEDEKAH program supported the department’s mission to improve education, research, and community service in Islamic economics. The program is a concrete way to serve the community. KAMISEDEKAH has both short-term and long-term programs. Short-term programs include: 1) Helping with emergency student tuition, 2) Disaster relief, 3) Gift-giving, 4) Revolving capital for students, 5) Mass circumcision funding, 6) Qurban (sacrifice) funding, 7) Orphan compensation, and 8) COVID-19 assistance. Long-term programs include: 1) Scholarships for the poor until graduation, 2) Opening kiosks, and 3) Establishing a FEBI clinic. The donation process works as follows: Every Thursday, students contribute IDR 2,000 each, which is collected by the class leaders and then submitted to the Department Student Association (HMJ) for Sharia Economics, Sharia Banking, and Sharia Insurance. Lecturers and staff contribute IDR 5,000 each, coordinated by the academic manager. The KAMISEDEKAH program aims to share resources and bring joy to everyone. The recipients' income varies, with the highest at IDR 2,250,000 and the lowest at IDR 600,000. On average, recipients earn IDR 1,000,000 per month. Most recipients have irregular jobs with low pay. The program helps ease their financial burden by allowing them to save money on daily expenses. In conclusion, the KAMISEDEKAH program contributes to the community's well-being and helps improve the lives of those in need.